Creating Frankenstein States: The Persistent Quest for the Ideal Modern Polity - Vinha, Luis da (Conjuntura Global, 2017)
The current paper argues that examining Mary Shelley’s Frankenstein provides a good analogy for understanding the current development of the international state-building agenda, particularly the underlying principles guiding intervention. In particular, the paper analyzes the Enlightenment Project’s quest for progress and perfection and how those ideas still thrive in the international organizations involved in post-conflict state-building interventions. The paper begins by analyzing the key characteristics underlying the Enlightenment’s search for global progress and peace. Subsequently, it identifies how modern international organizations have operationalized the principles and assumptions of the Enlightenment to promote world peace, particularly emphasizing its relationship to contemporary state-building operations.